Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.7554/elife.06041
|View full text |Cite
|
Sign up to set email alerts
|

A FYVE zinc finger domain protein specifically links mRNA transport to endosome trafficking

Abstract: An emerging theme in cellular logistics is the close connection between mRNA and membrane trafficking. A prominent example is the microtubule-dependent transport of mRNAs and associated ribosomes on endosomes. This coordinated process is crucial for correct septin filamentation and efficient growth of polarised cells, such as fungal hyphae. Despite detailed knowledge on the key RNA-binding protein and the molecular motors involved, it is unclear how mRNAs are connected to membranes during transport. Here, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
157
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(171 citation statements)
references
References 67 publications
11
157
0
Order By: Relevance
“…A loss of function causes no defects in general endosomal functions but causes defects in the recruitment of Rrm4, septin mRNA, and septin protein. As expected, this results in defective septin filament formation and in disturbed hyphal growth (193).…”
Section: The Fungal Cytoskeleton the Microtubule Cytoskeletonsupporting
confidence: 64%
“…A loss of function causes no defects in general endosomal functions but causes defects in the recruitment of Rrm4, septin mRNA, and septin protein. As expected, this results in defective septin filament formation and in disturbed hyphal growth (193).…”
Section: The Fungal Cytoskeleton the Microtubule Cytoskeletonsupporting
confidence: 64%
“…This might be needed for efficient formation of higher-order cortical filaments at the growing pole. Initially, we focused on Cdc3-GfpN because it exhibited the best biological activity, and in previous studies we have demonstrated in fluorescence recovery after photobleaching (FRAP) experiments that recovery of Cdc3-GfpN depends on Rrm4 Pohlmann et al, 2015). In this study, we were able to increase the spatial resolution and could resolve cortical filaments.…”
Section: Septins Are Co-delivered By Endosomesmentioning
confidence: 96%
“…The key factor for mRNA transport is the RNA-binding protein Rrm4, which contains three RNA recognition motifs (RRM) at the N-terminus and two peptide-binding MLLE-domains (Becht et al, 2005;Pohlmann et al, 2015). The MLLE domains interact with Upa1, an endosomal component that functions in recruiting Rrm4 to Rab5a-positive endosomes (Pohlmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different structure motifs on 358 mobile mRNAs may recruit specific RBPs at particular stages, or reciprocally, the 359 enrolled RBPs may induce a conformational change in mRNA structure for further 360 transport (Edelmann et al, 2017). The crucial roles of RBPs in the subcellular 361 localization of mobile mRNAs may be mediated by bridging mobile mRNAs to 362 endomembrane or cytoskeleton systems or be associated with motor proteins (Takizawa 363 et al, 1997;Schnorrer et al, 2000;Pohlmann et al, 2015). Indeed, analysis of RBPs in 364 phloem exudates identified multiple putative systemic RBPs involved in 365 phloem-mediated mRNA transport (Ham et al, 2009;Li et al, 2011 …”
mentioning
confidence: 99%